2001
DOI: 10.1034/j.1600-051x.2001.028007663.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease status of an indigenous population of Guatemala, Central America

Abstract: The study results highlight the importance of performing a detailed examination and appropriate analysis. In both studies, tooth retention was high (mean number of teeth recorded was 26.4 and 28.0 respectively), smoking unusual, and families large and localised to the village. This community thus affords several advantages over populations in developed countries when considering familial studies of adult periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 40 publications
6
43
0
6
Order By: Relevance
“…El CPITN es el segundo índice más utilizado en estudios epidemiológicos, siendo recomendado por la OMS. Sin embargo, no es un buen parámetro, ya que al ser un registro parcial -utiliza dientes índices-puede subestimar la extensión y gravedad de la enfermedad (13) , no describe las características de la enfermedad, no considera la movilidad dentaria ni la perdida de inserción, sobreestima las necesidades de tratamiento y subestima la magnitud y severidad de la enfermedad al ser un registro parcial, es decir, no determina la extensión ni la severidad de la enfermedad periodontal (14) . En cambio, el PSR al evaluar todos los dientes es un índice mejor que el CPITN.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El CPITN es el segundo índice más utilizado en estudios epidemiológicos, siendo recomendado por la OMS. Sin embargo, no es un buen parámetro, ya que al ser un registro parcial -utiliza dientes índices-puede subestimar la extensión y gravedad de la enfermedad (13) , no describe las características de la enfermedad, no considera la movilidad dentaria ni la perdida de inserción, sobreestima las necesidades de tratamiento y subestima la magnitud y severidad de la enfermedad al ser un registro parcial, es decir, no determina la extensión ni la severidad de la enfermedad periodontal (14) . En cambio, el PSR al evaluar todos los dientes es un índice mejor que el CPITN.…”
Section: Discussionunclassified
“…Un estudio de Dowsett y cols. en Estados Unidos indicó que el promedio de dientes en adultos entre 55-64 años fue de 24 dientes (14) , mientras que en Canadá, Galan y cols. encontraron que los adultos de 60 años tenían en promedio 8.2 dientes (17) .…”
Section: Discussionunclassified
“…87 Other longitudinal studies demonstrate these concepts; poorly controlled diabetics do not respond to periodontal therapy as well as controlled diabetics or non-diabetics. 88,89 Genetic factors play an important role in susceptibility to periodontal disease [90][91][92] as well as to systemic diseases. The impact of a poorly regulated immune response in fuelling the progression of periodontal destruction secondary to bacterial plaque is well documented.…”
Section: An Overview Of Periodontitis and Dmmentioning
confidence: 99%
“…Overall, 58% of the subjects had a positive fingernail result, with a significant positive relationship between fingernail and tongue positivity. the authors have suggested that oral carriage of H. pylori may play a role in the transmission of infection and that the hand may be instrumental in transmission (7).…”
Section: Pylori In the Oral Cavity And The Role Of The Dentists In LImentioning
confidence: 99%